2017
DOI: 10.20319/pijss.2017.33.174197
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Planning and Performance Measurement for Public Universities in Sulawesi, Indonesia;quantitativeapproach

Abstract: The purpose of the study is to examine the real process of strategic planning and performance measurement within public universities in Sulawesi, Indonesia. The specific objective is to focus on strategic planning, performance measurement and associate the findings with the objectives of Higher Education Long Term Strategy from Indonesian Directorate General Higher Education. Quantitative methodology approach with an empirical survey was conducted based on questionnaires. The findings revealed that the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
5
0
4
Order By: Relevance
“…Equally, Esfahani et al (2018) confirmed a positive link between vision statements and organizational performance in healthcare organizations in Iran. Similarly, Similarly, Usoh and Preston (2017) confirmed a positive relationship between mission statement internalization and organizational performance in Public Universities in Sulawesi, Indonesia. In Spain, Revilla and Desiree (2012) established that team vision in combination with organizational context, built upon a learning culture and trust positively influence product development performance.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Equally, Esfahani et al (2018) confirmed a positive link between vision statements and organizational performance in healthcare organizations in Iran. Similarly, Similarly, Usoh and Preston (2017) confirmed a positive relationship between mission statement internalization and organizational performance in Public Universities in Sulawesi, Indonesia. In Spain, Revilla and Desiree (2012) established that team vision in combination with organizational context, built upon a learning culture and trust positively influence product development performance.…”
Section: Introductionmentioning
confidence: 57%
“…Several other scholars have examined the relationship between articulation of organizational purpose and organizational performance (Alosani et al, 2019;Donkor, Donkor, & Kwarteng, 2018;Esfahani, Mosadeghrad, & Akbarisari, 2018;Namada, Bagire, Aosa, & Awino, 2017;Usoh & Preston, 2017). In their study, Alosani et al (2019) confirmed a positive link between focus on organizational purpose and the performance of the Dubai Police.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…b. Pengukuran Kinerja Organsiasi, pengukuran kinerja organisasi publik seperti perguruan tinggi telah mendapat perhatian yang luas di kalangan akademisi. Misalnya (Usoh, 2017), (Abdullah, 2006) (Kaplan & Norton, 1992) Model pengukuran kinerja organisasi yang banyak digunakan adalah Balanced Scorecard atau yang sering disingkat dengan BSC. BSC adalah pengukuran kinerja organisasi yang komprehensif karena mencakup aspek finansial dan non-finansial.…”
Section: Kinerja Organisasiunclassified
“…Em um cenário em que as estratégias de decisão sobre a aplicação de recursos orçamentários/financeiros pelas universidades federais podem se revelar sob as mais diversas orientações gerenciais, questiona-se: quais os efeitos do modelo de alocação e distribuição orçamentária no desempenho organizacional das universidades federais brasileiras? Dito isso, infere-se que os gestores, ao decidirem realocar os recursos de forma distinta do que a priori foi estabelecido pela matriz, interferem no desempenho da própria universidade de forma diferente, reforçando a necessidade de alinhar o planejamento estratégico e a avaliação de desempenho (Usoh & Preston, 2017). É oportuno ressaltar que os critérios de alocação e distribuição dos recursos para as universidades são pautados em resultados e indicadores de qualidade, embora a gestão das universidades conte com autonomia para os destinar a áreas que julgar mais importantes ou estratégicas -exceto para os recursos destinados à folha de pagamento de servidores ativos e inativos.…”
Section: Introductionunclassified